Influence of Time of Mission on Correct Diagnosis by the Prehospital Emergency Physician: A Retrospective Study. (2nd April 2019) - Ramadanov, Nikolai; Klein, Roman; Ramadanova, Nevena; Behringer, Wilhelm
Abstract : Objectives . The objective of this retrospective study was to examine the diagnostic matching (DM) between the prehospital diagnosis by the prehospital emergency physicians and the hospital discharge diagnosis, adjusted for time of mission. Methods . Over a period of 12 months, all patient care reports of the emergency medical services in Bad Belzig were examined. By systematically comparing the prehospital suspected diagnosis to the discharge diagnosis, the DM was determined after careful examination of the entire course of each patient's case, blinded to time of mission. The results were tested for statistically significant results using the Chi-square test for nominal data and the Mann-Whitney U test for nonnormally distributed independent samples. Results . The DM occurred in 52%, it occurred partially in 24%, and it did not occur in 24% of 580 included cases. The DM showed clear fluctuation over 24 hours, with the worst results at 4 and 5 a.m. and the best results at 6 a.m. and 3 p.m. Conclusions . The DM appears to depend directly on the time of mission. Decreased performance and concentration at night might be a cause for incorrect diagnoses by prehospital emergency physician in the early morning hours. Future studies need to investigate the effect of different shift planning on performance.